2012
DOI: 10.1590/s2179-64912012000400015
|View full text |Cite
|
Sign up to set email alerts
|

Influência de altura, peso e índice de massa corporal na força axial da língua

Abstract: OBJETIVO: Analisar a influência de peso, altura e índice de massa corporal na força axial da língua. MÉTODOS: Foram analisados os prontuários referentes a 44 indivíduos com idade entre 20 e 37 anos, sendo 11 (25%) homens e 33 (75%) mulheres. Foram pesquisadas as informações referentes a peso, altura, resultado da avaliação clínica da língua (tônus lingual) e resultado da avaliação instrumental da força axial da língua, sendo esta última realizada por meio do FORLING. Os dados foram analisados estatisticamente.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Perceptual evaluation is subjective and depends on the examiner's good judgment and experience, whereas instrumental assessment is performed using instruments that provide numerical data on tongue force or pressure, but most tools are not commercially available in Brazil. For this reason, the Biomechanical Engineering Group of the Universidade Federal de Minas Gerais (UFMG) developed an instrument to measure the axial force of the tongue that has already been used in several studies (1,2,(11)(12)(13)(14)(15)(16)(17) . The portable version of the Forling instrument was designed later (18) , and is currently undergoing testing.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual evaluation is subjective and depends on the examiner's good judgment and experience, whereas instrumental assessment is performed using instruments that provide numerical data on tongue force or pressure, but most tools are not commercially available in Brazil. For this reason, the Biomechanical Engineering Group of the Universidade Federal de Minas Gerais (UFMG) developed an instrument to measure the axial force of the tongue that has already been used in several studies (1,2,(11)(12)(13)(14)(15)(16)(17) . The portable version of the Forling instrument was designed later (18) , and is currently undergoing testing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the current patient's BMI had decreased meaningfully from approximately 25 to 21 while on CPAP during the 18 months preceding the initiation of tamsulosin therapy. A significant weight loss in an OSA patient beginning with a normal-range BMI could perhaps unfavorably alter genioglossus mass or strength [31], [32]. If so, then in this patient any sensitivity to adverse muscular effects from α 1 -adrenergic blockade may have been increased.…”
Section: Discussionmentioning
confidence: 98%
“…Obese patients may experience changes to their stomatognathic system, which includes the lips [4], and exercises such as lip closure can help increase lip strength and mobility over time, potentially aiding swallowing [5]. Recent studies have shown a relationship between maximum tongue pressure and BMI [20,21], and the influence of height, weight, and BMI on axial tongue muscle strength [22]. Moreover, tongue pressure has also been related to dental arch length and width, BMI, and weight [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a relationship between maximum tongue pressure and BMI [20,21], and the influence of height, weight, and BMI on axial tongue muscle strength [22]. Moreover, tongue pressure has also been related to dental arch length and width, BMI, and weight [22,23]. Therefore, it is possible that the force used to close the lips and the pressure on the tongue are intermediate factors in chronic diseases that are thought to be caused by being overweight/obese.…”
Section: Discussionmentioning
confidence: 99%